Gending Gilak 32 Ketukan Sebagai Strategi Pembelajaran Karawitan Bali Bagi Siswa Pemula SMK Negeri 5 Denpasar - I Putu Cory Arsatama; I Gede Mawan (Jayapangus Press, 2026)
Balinese karawitan learning at the vocational high school level still faces significant challenges, especially for students who have no prior experience or initial interest in playing gamelan, resulting in low understanding of basic concepts and karawitan technical skills. Few studies have specifically examined the use of particular gamelan repertoire as a structural medium for beginner students at the vocational high school level. This study aims to describe the implementation of a Balinese karawitan learning strategy based on Gending Gilak 32 beats to improve the learning outcomes of Grade X Seni Karawitan students at SMK Negeri 5 Denpasar. This study employed a qualitative descriptive approach with 29 students as research subjects. Data were collected through observation, interviews, and documentation of student practical assessment results. The learning strategy was implemented through six stages: gamelan instrument introduction, basic gangsa technique demonstration, guided practice in small groups, repetitive practice, individual practical evaluation, and learning reflection. The findings indicate that the implementation of the learning strategy through Gending Gilak 32 beats effectively improved students' understanding of basic concepts and karawitan technical skills. Prior to the implementation of the strategy, the class average score stood at 66.65 with all 29 students failing to meet the Minimum Competency Criteria (KKM) of 75. Following the implementation, the class average increased to 82.00 with all students declared competent, reflecting an improvement of 15.35 points. The improvement was not only quantitative but also qualitative, marked by increased student confidence, accuracy of tabuhan patterns, tempo stability, and mastery of the four basic gangsa techniques. This study contributes theoretically by affirming that simply structured repertoire can function as effective musical scaffolding within the context of formal Balinese karawitan pedagogy, and can serve as a reference for karawitan arts teachers in delivering foundational material to beginner students at the vocational high school level.